THE IMPORTANCE OF INTERACTIVE GAMES IN ENGLISH LANGUAGE CLASSES - Xolmatova Zilola, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article discusses the importance of interactive games in English language classes and their impact on students’ learning motivation and language skills. Interactive games help learners improve speaking, listening, reading, and writing abilities in an engaging and effective way. The article also highlights modern teaching methods, the role of technology in language education, and the advantages of game-based learning in creating an active classroom environment.